WTE plants installed in European cities. A review of success stories. Issue 5 (8th August 2016) - Chaliki, Paraskevi; Psomopoulos, Constantinos S.; Themelis, Nickolas J.
Abstract : Purpose: Waste is a resource. Generating energy from waste instead of sending it to landfill avoids methane gas which equals 25 times CO2 in mass. In combination with the energy efficiency thresholds set in Waste Framework Directive, this could prevent up to a further 45 million tons of CO2eq per year. This paper presents the waste to energy plants installed in 10 European cities which have been selected among the most sustainable cities or among the best cities to live in. Design/methodology/approach: The work is based on literature review and a combination of several statistical data and reports that include the required data. Findings: The European Directives, along with the general thinking that wastes are resources and the effort to reduce the environmental impact in urban environment from waste management, were the driving forces. The most sustainable cities in EU considered that their sustainability is based also in energy recovery from wastes. All of them are using Waste-to-Energy facilities to treat a significant part of their waste in order to produce energy in the form of heat and electricity. And they do it in a very successful and environmental friendly way, as they mainly utilise the waste fractions that cannot be recycled or reused, and they do not landfill these resources. This approach is proving that the sustainable waste management cannot be achieved without Waste-to-Energy facilities, since a fraction of wastes consists of non- recyclable and non reusable materials, which present significant heating value that cannot be neglected as an energy source. Originality/value: This paper presents the waste – to – energy plants installed in 10 European cities which have been selected among the most sustainable cities or among the best cities to live in. This work aims to present the strong and successful relation between waste – to – energy and sustainability in the modern complex urban environment.